Criticism and Satire in the Comic Strip @komik.grontol on Instagram Related to Indonesian Government Policies (A Pragmatic Semiotic Study) - Santuso, Santuso; Sukarno, Sukarno (Eastasouth Institute, 2025)
Comic strips, beyond entertainment, serve as a medium for expressing public aspirations. This study explores criticism and satire of government policies perceived as unfavorable to the people. Using a qualitative descriptive approach, the research examines linguistic data from the Instagram account @komik.grontol, covering content from December 2024 to February 2025. Data collection was conducted through documentation techniques, and analysis followed the theory of conversational implicature and semiotics. The findings reveal various criticisms, including (a) the 12% VAT increase, (b) the construction of fences and the granting of HGB permits for Laut Tangerang, (c) the appointment of special staff amid budget efficiency efforts, (d) lenient punishments for corrupt officials, (e) the LPG sales policy that burdens the public, (f) the prohibition of students from criticizing meal quality in the MBG program, and (g) the proposal to introduce insects as a protein source in the MBG program. These findings have theoretical implications for the development of pragmatics and visual communication studies, as well as practical implications for the government to be more responsive to public criticism and for creators to convey messages in an ethical and educational manner.